Metoda Obszarów Częściowych dla Zagadnień Przewodnictwa Cieplnego - Thrun, Z. (Engineering Transactions, 1965)
The method described concerns non-stationary problems. The region under consideration is divided into a number of sub-regions. Solution is sought-for in the form of a sum of products of appropriate approximating functions, the number of products being equal to that of sub-regions. The method is applicable to problems with any initial temperature and any boundary conditions. for bodies of arbitrary nonhomogeneous thermal properties.